Corak Pemahaman dalam Visualisasi Hadis: Studi Kasus Animasi Hadis pada Channel Youtube CulapCulip - Andi Mujahidil Ilman SM (Pascasarjana, Universitas Islam Negeri Alauddin Makassar, 2024)
The rapid progress of information technology has made people make more use of online media in carrying out their daily activities. The ease of access to communication through online media makes Indonesia the country with the fourth ranking of internet users in the world. There are various social media platforms that can be used to find information, including YouTube. Apart from being a learning medium, YouTube has become a means for everyone to get the information they need from various parts of the world. Islamic Da'wah content is often found in YouTube uploads, both in the form of recordings and animations.